Characteristics of Multi-tier Hybrid Dryer for Drying Corn Grains - Allo, Rombe; Pongsapan, Allo Sarira; Mangallo, David; Agustinus; Siregar, Samuel Parlindungan; Pagasis, Thomas; Werdhani, Anastasia Sri; Numberi, Johni Jonatan; Palamba, Pither; Banda, Dionisius Desriadi; Joni (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2024)
The type of drying device known as a hybrid dryer is a tool that harnesses solar energy and the heat generated by a biomass fuel-powered heat exchanger. This study was conducted to assess the performance of the hybrid dryer by analyzing the parameters of the device itself and the dried material. The research was carried out experimentally using a solar collector and a biomass furnace (as a heat exchanger) to heat the air. The solar collector used consists of 0.35 mm thick, black-painted zinc, coated with 5 mm thick glass, and installed at a 20-degree angle. The heat exchanger pipe used has a diameter of 1.25 inches and is made of galvanized pipe. The tested sample is corn seeds with an initial moisture content of about 24.6%. The experimental results show that in the drying process using a solar dryer, the initial moisture content of 24.8% was successfully reduced to 14% at 5.50 h (rack 1), 6.50 h (rack 2) and 7.00 h (rack 3) with a thermal efficiency of 24.25%. Meanwhile, in the hybrid drying process, the required time is approximately 5.00 h (rack 1), 5.50 h (rack 2) and 6.00 h (rack 3), with a efficiency of the drying equipment used is 21.048±5.690% (hybrid) and 22.706±6.437% (solar).